AI Literacy Needs Assessment and Development Guidelines for Secondary School Administrators in Thailand - Sukhamsri, Chadawan; Unkong, Thidawan; Jansila, Vithaya; Suaklay, Narissara (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This study aimed to (1) study the needs assessment for developing artificial intelligence (AI) literacy among secondary school administrators under the Office of the Basic Education Commission in Thailand, and (2) study the guidelines for developing AI literacy among secondary school administrators in Thailand. The sample consisted of administrators from secondary schools under the Office of the Basic Education Commission (OBEC). Using Yamane’s formula (1973) at a 95% confidence level, a sample of 342 schools was determined. Multi-stage sampling was employed by stratifying schools by region and school size. Data were collected using a needs assessment questionnaire on AI literacy and semi-structured interview guidelines for exploring development approaches. Quantitative data were analyzed using descriptive statistics and the Modified Priority Needs Index (PNIModified), while qualitative data were analyzed through content analysis. The research results were found as follows. 1. The overall needs assessment for developing AI literacy among secondary school administrators in Thailand showed a needs index (PNIModified = 0.351). When considered by individual aspects, the area with the highest need for development was using AI (PNIModified = 0.361), followed by knowing AI (PNIModified = 0.360), understanding AI (PNIModified = 0.353), evaluating AI (PNIModified = 0.352), and AI ethics (PNIModified = 0.327), respectively. 2. A study on guidelines for developing AI literacy among secondary school administrators in Thailand derived from this research encompassed four key components: a development principle grounded in the 70-20-10 learning model; three development methods comprising expert briefing, workshop, and field study trip; a four-level evaluation framework based on the Kirkpatrick Model; and success conditions including adequate resource allocation, continuous professional learning, and a culture of embracing innovation.